Instrumentation development for the measurement and characterisation of indoor and urban canyon ambient noise floor in the Galileo frequency bands - Junered, Marcus; Akos, Dennis; Adjrad, Mounir; Aguado, Enrique; Daly, Michael; Kemp, Andrew (Luleå tekniska universitet, EISLAB, 2006)
The Galileo satellite navigation system will offer new frequency bands as well as share existing spectrum with parallel systems. The development of the Galileo system will significantly improve the already high level of accuracy, availability, reliability and integrity provided by current satellite navigation systems. However, in urban canyon and indoor locations there is a significant performance loss due to high levels of attenuation, signal masking and multipath. Receiver design for positioning in challenging areas like this is dependent on accurate characterization of the signal andnoise environments. Effects of signal propagation into urban canyons and indoors is relatively well known. However, the noise characteristics are largely unknown, especially the effect on the noise floor in the sensitive Galileo bands from the proliferation of electronic devices. This paper describes the design and development of a measurement instrument to characterise the underlying thermal interference noise floor in the various frequency bands in which Galileo will operate. The design trade-offs and designs are presented along with initial instrument testing. The instrument will be used in a joint measurements campaign between Luleå Technical University and the University of Leeds. Godkänd; 2006; Bibliografisk uppgift: Titel på proceedings: Proceedings of the 3rd ESA Workshop on Satellite Navigation User Equipment Technologies, NAVITEC; 20070405 (junered)